Application of microbial membrane tetraether lipids in speleothems - Zang, Jingjie; Yang, Huan; Zhang, Jiahao; Tang, Huiru; Tan, Liangcheng (Frontiers in Ecology and Evolution, 2023)
Glycerol dialkyl glycerol tetraethers (GDGTs), which are derived from microbial membranes, occur widely in soils, peats, lake sediments, marine sediments, hot springs, and other environments. GDGTs respond sensitively to environmental changes and have become an important tool in paleoenvironmental reconstruction. However, their application in speleothems, one of the most important archives of the study of past climates, has been quite limited. In this paper, we review the recent progress in the study of GDGTs in speleothems, from their sources to their distribution characteristics and paleoenvironmental applications. GDGTs in speleothems have been shown to come from dripping water, and cave systems. The distribution of GDGTs in speleothems shows that archaeal isoprenoid GDGTs (isoGDGTs) dominate over bacterial branched GDGTs (brGDGTs). The proxies based on isoGDGTs (TEX86) and brGDGTs (MBT/CBT) are correlated with temperature, which may offer promising potential methods for reconstructing terrestrial palaeotemperature. Ultimately, we discuss the difficulties and problems to be solved in studying speleothem GDGTs and the possible future directions for this field.